Intercellular pectic protuberances in leaves of some Xyris species (Xyridaceae) - Machado, SR; Sajo, M. G. (Natl Research Council Canada, 1996)
Mature leaves of eight species of Xyris were prepared by standard methods for electron transmission microscopy. Wartlike intercellular pectic protuberances were observed on the surface of inner periclinal walls of epidermal cells in Xyris obcordata, Xyris hymenachne, and Xyris pterygoblephara. In the latter, the protuberances also occur on the surface of parenchymatic mesophyll cells; they frequently project into intercellular spaces and may connect opposing cells. For the genus Xyris, the intercellular pectic protuberances may be considered taxonomically significant at the species level.
Keywords: Xyris; Xyridaceae; pectin; cell wall